1986
DOI: 10.1139/z86-372
|View full text |Cite
|
Sign up to set email alerts
|

The eggshell of Drosophila melanogaster. V. Structure and morphogenesis of the micropylar apparatus

Abstract: The micropylar apparatus in Drosophila melanogaster consists of two parts. The inner part is a protrusion of vitelline membrane, whereas the outer part is a chorionic protrusion containing a canal, through which the spermatozoon enters. In the formation of the micropylar apparatus two follicle cell subpopulations are involved: the border cells, i.e., a group of 9 follicle cells, and the peripheral cells (about 36 cells). The morphogenesis of the micropyle starts at stage 10B, when the border cells secrete the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0
1

Year Published

1986
1986
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 0 publications
1
24
0
1
Order By: Relevance
“…The projection comprises numerous microtubules and forms a barrier to the deposition of egg envelopes, which results in the formation of a micropylar canal (Hart, 1990). The same has been observed in numerous insect groups (Yamauchi & Yoshitake, 1984; Zarani & Margaritis, 1985, 1991; Wenzel et al , 1990; Kubrakiewicz et al , 2005).…”
Section: Introductionsupporting
confidence: 82%
“…The projection comprises numerous microtubules and forms a barrier to the deposition of egg envelopes, which results in the formation of a micropylar canal (Hart, 1990). The same has been observed in numerous insect groups (Yamauchi & Yoshitake, 1984; Zarani & Margaritis, 1985, 1991; Wenzel et al , 1990; Kubrakiewicz et al , 2005).…”
Section: Introductionsupporting
confidence: 82%
“…The micropyle is a narrow channel that extends at an oblique angle from the ventral aspect of the operculum and functions as the sperm entry point during fertilization. After their respective migrations, the border cells and leading edge centripetal cells come together at the anterior of the oocyte to construct this channel (Zarani and Margaritis, 1986). Manipulations that prevent border cells from reaching the oocyte have shown that the centripetal cells play the major role in the construction of the cone projecting from the front of the egg, whereas the border cells create a pore within the cone for sperm entry (Montell et al, 1992).…”
Section: Formation Of Specialized Eggshell Structuresmentioning
confidence: 99%
“…At the which facilitates sperm entry (Zarani and Margaritis 1986). snd (stage 14A) the appendages exhibit two distinct sides with Initially at stage 10B, a number of cells secrete the paracrystalplaques and a network, respectively.…”
Section: Specialized Regionsmentioning
confidence: 99%
“…formation is facilitated by the existence of the liquid crystal like or paracrystalline region. The rest of the micropylar apparatus is formed by migrating peripheral cells and by means of microtubular protrusions which make the micropylar canal (Margaritis 1984;Zarani and Margaritis 1986).…”
Section: Specialized Regionsmentioning
confidence: 99%